The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.analchem.6b00393
|View full text |Cite
|
Sign up to set email alerts
|

Polymers as Reference Partitioning Phase: Polymer Calibration for an Analytically Operational Approach To Quantify Multimedia Phase Partitioning

Abstract: Polymers are increasingly applied for the enrichment of hydrophobic organic chemicals (HOCs) from various types of samples and media in many analytical partitioning-based measuring techniques. We propose using polymers as a reference partitioning phase and introduce polymer-polymer partitioning as the basis for a deeper insight into partitioning differences of HOCs between polymers, calibrating analytical methods, and consistency checking of existing and calculation of new partition coefficients. Polymer-polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 47 publications
3
53
0
1
Order By: Relevance
“…In general, these silicone rubber-water partition coefficients are not very high but in agreement with reported/calculated logK p values of 3.71 ‡ . In general, lower logK pw have been reported for SSP silicone rubber than for AlteSil™ (Gilbert et al 2016). This is also the case for TDBrPP.…”
Section: Polymer-water Partition Coefficient Kpw For Tdbrppmentioning
confidence: 82%
“…In general, these silicone rubber-water partition coefficients are not very high but in agreement with reported/calculated logK p values of 3.71 ‡ . In general, lower logK pw have been reported for SSP silicone rubber than for AlteSil™ (Gilbert et al 2016). This is also the case for TDBrPP.…”
Section: Polymer-water Partition Coefficient Kpw For Tdbrppmentioning
confidence: 82%
“…Loading methods based on solvent evaporation have previously been used for passive dosing with halogenated and non-halogenated aromatic chemicals. 42,43 Also, recently Gilbert et al 44 loaded silicone polymers with PCBs using isooctane, which was thereaer allowed to evaporate. To conrm that all loading solvent had evaporated, the weight of dosing vials (n ¼ 9) containing 0.03 g of polymer was determined before loading and aer evaporation of the solvent.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Hence, partition coefficients are polymer-specic as the content of different additives and llers (e.g. diatomaceous earth 44 ) may vary between suppliers and thus cause differences in partitioning properties. In an extensive review by DiFilippo et al, 56 it was concluded that improper measuring techniques were a main source of error for the K p-w and as opposed to Smedes et al, no signicant effect associated with the supplier of the polymers was found.…”
Section: Determination Of K Pdms-wmentioning
confidence: 99%
“…The accuracy of Kpw might explain a large fraction of the uncertainty in PSMs (Lydy et al, 2014) because accurate determination of high Kpw values for HOCs is challenging. Recently, Gilbert et al (2016) proposed to measure and use polymer-polymer partition coefficients for calibration, property evaluation, and data consistency tests of multiple passive samplers. This is a promising approach for the consistency test of sediment passive samplers because polymer-polymer partition coefficients can be much more accurately measured than polymer-water partition coefficients (Gilbert et al, 2016), primarily due to the fact that the error-prone measurement of low aqueous phase concentrations can be avoided.…”
Section: Cfree = Cp/kpwmentioning
confidence: 99%